Iatrogenic diaphragmatic hernia in infants: Potentially catastrophic when overlooked - Yousef El-Gohary; Isaiah Schuster; Richard J. Scriven; Charles V. Coren; Edmund Kessler (Elsevier, 2014)
Acquired diaphragmatic hernias are a rare occurrence. They can result from blunt, penetrating or inadvertent iatrogenic injury. When overlooked they can potentially be catastrophic. We report a case of iatrogenic diaphragmatic hernia in a six-month old infant presenting with acute respiratory distress as a result of strangulated bowel herniating into the left hemithorax caused from a traumatic chest tube insertion in the neonatal period.